PENGARUH ONLINE CUSTOMER REVIEW, ONLINE CUSTOMER RATING, DAN CASH ON DELIVERY TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA E-COMMERCE TOKOPEDIA - Kawet, Raymond Christian; Palandeng, Indrie Debbie; Pitta, Raymond V. (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to determine the effect of Online Customer Review, Online Customer Rating, and Cash On Delivery on product purchase decisions on Tokopedia e-commerce simultaneously or partially. This research approach uses quantitative methods. With a population study on Consumers Who Use the Tokopedia application. The sample in this study was 98 respondents. In this study the data were analyzed using multiple linear regression, with analysis test tools used IBM SPSS Version 25. The results of the analysis show that Online Customer Reviews, Online Customer Ratings, and Cash On Delivery On Purchase Decisions Simultaneously Influence. Online Customer Review partially has an insignificant effect on product purchase decisions on Tokopedia e-commerce. Online Customer Rating partially has a significant effect on product purchase decisions on Tokopedia e-commerce. Cash On Delivery partially has a significant effect on product purchase decisions on Tokopedia e-commerce. Suggestions for research are expected to sellers or vendors in Tokopedia to better understand what is the determinant of customers and provide the best for customers so that customers can improve purchase decisions through sellers or vendors in Tokopedia, by utilizing online customer reviews, online customer ratings, and cash on delivery strategically.